2013
DOI: 10.1002/bip.22244
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and performance of short cationic antimicrobial peptide isomers

Abstract: Cationic antimicrobial peptides (CAMPs) represent an ancient defense mechanism against invading bacteria, with peptides such as the cathelicidins being essential elements of vertebrate innate immunity. CAMPs are typically associated with broad-spectrum antimicrobial potency and limited bacterial resistance. The cathelicidin identified from the elapid snake Naja atra (NA-CATH) contains a semi-conserved repeated 11-residue motif (ATRA motif) with a sequence pattern consistent with formation of an amphipathic hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 40 publications
3
22
0
Order By: Relevance
“…Residues Val27 to Thr31 are predicted to adopt an extended structure. Previously, circular dichroism data have indicated that the peptide and the shorter ATRA-1A construct adopt a stable helical conformation in 50% TFE [19,46].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Residues Val27 to Thr31 are predicted to adopt an extended structure. Previously, circular dichroism data have indicated that the peptide and the shorter ATRA-1A construct adopt a stable helical conformation in 50% TFE [19,46].…”
Section: Resultsmentioning
confidence: 99%
“…Given that the peptide has been observed interacting with membranes [19,44,46,49], we next have investigated whether the peptide would adopt a stable structure in the presence of 80:20 DOPC:DOPG liposomes, which serve as a mimic of the bacterial membranes (Fig. 1B).…”
Section: Nmr Studies Of Na-cathmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the mechanism of AMP action is unknown and pore formation in cell membranes may be responsible for lytic ability, it is well established that AMP interact directly with the cell membrane surface and are able to enter the lipid bilayer, resulting in cell membrane disruption and leakage of cytoplasmic components which leads to killing of microbes (Lee et al 2010;Izadpanah and Gallo 2005;Lorenzon et al 2012;Sani et al 2013). AMP have attracted much attention as an alternative to antibiotics because of their effect against bacterial infections and drug resistant bacteria (Juba et al 2013;AnayaLopez et al 2013).…”
Section: Introductionmentioning
confidence: 97%
“…For example, de Latour and coworkers (2010) produced a series of very short peptides that were derived from the Naja atra cathelicidin, containing the so-called ATRAmotif [KR(F/A)KKFFKK(L/P)K], and demonstrated their low toxicity to host cells and high-potent antimicrobial activity against Gram-negative bacteria. The efficacy test of short d-enantiomer peptides that were derived from ATRA-motif indicates that these isomeric peptides exhibit varied potencies against bacterial strains and that helicity propensity (conformational helix) depends on the anionic content of the membranes (Juba et al 2013). The modulation of the structure and function of snake venom cathelicidin can also be ascertained by BF-15, a 15-mer peptide that was derived from cathelicidin-BF (BF-30) and that maintains an amphipathic a-helix and potent antimicrobial activity against antibiotic-resistant bacteria but exhibits reduced hemolytic activity (Chen et al 2011b).…”
Section: Vipericidins and Snake Venom Cathelicidin-related Peptidesmentioning
confidence: 99%